UNFAIR ACTION AND ITS LEGITIMATION IN INTERNATIONAL SPACE: PHILOSOPHICAL AND LEGAL CONTEXT - Kharchenko, S. P. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
This investigation is devoted to the conceptualization of the "unfair action" phenomenon; determination of mechanisms of its legitimation in international space. The article states that understanding of fairness in primitive society was associated with unconditional execution of certain rules, regulations. In ancient Greece, the concept of "benefit" was remotely equal to fairness. In public mind, the concept of "benefit" slowly converted into the demand for a punishment for the breach of a general rule. Over time, the model of benefit was converted into a more sophisticated practice of empowering people. It is described that Christian morality allowed the equality of all people before the God. Feudal morals laid the basic proportional fairness. The quintessence of this model was the "noble origin". In bourgeois society fairness provided legal equality of individuals in civil society. Gradually political, legal, economic, academic institutions were formed. Modern ethical debates are focused on theories of fairness within which individuals in their social life are seen as interconnected elements, both mutually needed and in that sense, equal to each other. Individuals, living in the community, form a whole, a society, with common goals and interests.In general, in a broad sense, unfairness is the folly of public life; it can be defined as the common denominator of all socially immoral disordered relations among people, as the last immoral-appeal instance in public affairs. It coincides with the immorality in its projection on the social sector; it is the lack of virtue in social institutions.